Academic Emergency Medicine Physicians' Anxiety Levels, Stressors, and Potential Stress Mitigation Measures During the Acceleration Phase of the COVID‐19 Pandemic. (21st July 2020) - Rodriguez, Robert M.; Medak, Anthony J.; Baumann, Brigitte M.; Lim, Stephen; Chinnock, Brian; Frazier, Remi; Cooper, Richelle J.
Abstract: Objective: The objective was to assess anxiety and burnout levels, home life changes, and measures to relieve stress of U.S. academic emergency medicine (EM) physicians during the COVID‐19 pandemic acceleration phase. Methods: We sent a cross‐sectional e‐mail survey to all EM physicians at seven academic emergency departments. The survey incorporated items from validated stress scales and assessed perceptions and key elements in the following domains: numbers of suspected COVID‐19 patients, availability of diagnostic testing, levels of home and workplace anxiety, severity of work burnout, identification of stressors, changes in home behaviors, and measures to decrease provider anxiety. Results: A total of 426 (56.7%) EM physicians responded. On a scale of 1 to 7 (1 = not at all, 4 = somewhat, and 7 = extremely), the median (interquartile range) reported effect of the pandemic on both work and home stress levels was 5 (4–6). Reported levels of emotional exhaustion/burnout increased from a prepandemic median (IQR) of 3 (2–4) to since the pandemic started a median of 4 (3–6), with a difference in medians of 1.8 (95% confidence interval = 1.7 to 1.9). Most physicians (90.8%) reported changing their behavior toward family and friends, especially by decreasing signs of affection (76.8%). The most commonly cited measures cited to alleviate stress/anxiety were increasing personal protective equipment (PPE) availability, offering rapid COVID‐19 testing at physician discretion, providing clearer communication about COVID‐19 protocol changes, and assuring that physicians can take leave for care of family and self. Conclusions: During the acceleration phase, the COVID‐19 pandemic has induced substantial workplace and home anxiety in academic EM physicians, and their exposure during work has had a major impact on their home lives. Measures cited to decrease stress include enhanced availability of PPE, rapid turnaround testing at provider discretion, and clear communication about COVID‐19 protocol changes.